2020
DOI: 10.1016/j.scitotenv.2020.138761
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the measures to flatten the epidemic curve of COVID-19. The case of Spain

Abstract: After the cases of COVID-19 skyrocketed, showing that it was no longer possible to contain the spread of the disease, the governments of many countries launched mitigation strategies, trying to slow the spread of the epidemic and flatten its curve. The Spanish Government adopted physical distancing measures on March 14; 13 days after the epidemic outbreak started its exponential growth. Our objective in this paper was to evaluate ex-ante (before the flattening of the curve) the effectiveness of the measures ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
128
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(154 citation statements)
references
References 4 publications
5
128
0
7
Order By: Relevance
“…Saez et al. [21] identified a reduction in the rate of infection in Spain after different measures of physical distance, including travel flow. With the advance of the outbreak, local interventions such as lockdown, hygiene, curfew, mass examinations of the population are more efficient.…”
Section: Discussionmentioning
confidence: 99%
“…Saez et al. [21] identified a reduction in the rate of infection in Spain after different measures of physical distance, including travel flow. With the advance of the outbreak, local interventions such as lockdown, hygiene, curfew, mass examinations of the population are more efficient.…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 is a global health emergency that is going to change the way in which people, institutions and governments manage their lives and duties. The fact that there is no known specific drugs or vaccines for COVID-19 until now raises the importance of behavioral strategies, such as social distancing, lockdowns [2][3][4][5][6][7] and mass testing [8,19,20] in the fight against the pandemic. Our results show that the LR of COVID-19 in Brazil raised since the beginning of pandemic and reach a percentual value of 7.0 ± 0.2 %.…”
Section: Discussionmentioning
confidence: 99%
“…During the rst peak of the pandemic, affected countries chose different levels of interventions based, among others, on national risk assessments of estimated number of patients and capacity for hospitalization and critical care support [8,9]. The evolution of the pandemic over the last months demonstrated that timely interventions were effective to delay the spread of COVID-19 [10,11], as it was also shown in previous u and SARS epidemics [12][13][14].…”
mentioning
confidence: 93%